Clinical trials in otology and neurotology: state of the science - Lindsay S. Moore; Varun Sagi; Konstantina M. Stankovic; Konstantina M. Stankovic; Konstantina M. Stankovic (Frontiers in Neurology)
ObjectiveTo evaluate the current state of interventional clinical trials in otology and neurotology.Study design/methodsReview of registered clinical trials on ClinicalTrials.gov from January 1st 2019 through May 31st 2025. Interventional trials and those that met keyword criteria for otologic/neurotologic disorders were included. For each study, key characteristics including trial status, trial phase, study design, participants, intervention type, funding source, and results status were collected.SettingNational database.ResultsThough the number of interventional otologic and neurotologic clinical trials has grown over the past 15 years, in the past 5 years, there has been a stagnation of the steady growth seen in the preceding ten. The greatest proportion of trials were focused on hearing loss, utilized devices, were randomized, and were funded by sources other than industry or the government. Compared to 2008–2018, trends included a shift towards device and procedural interventions for vestibular disorders and a decrease in device trials and increase in behavioral interventions for tinnitus. Emerging areas include novel pharmacological and gene therapies for hearing loss and vestibular schwannoma, but these areas remain gaps and are promising therapeutic avenues that merit further exploration.ConclusionFuture interval assessments exploring the trends in otologic and neurotologic clinical trials should be performed to identify gaps that offer opportunities for innovation of novel therapies and to monitor the health of the clinical trial environment.